LEGAL SYSTEM UNDER THE TALIBAN - Rasheed Ullah Shinwari; Mateeullah Rahimi; Sayed Israr Samim; Sayed Abdul Hakim Hikmat (Policy Research Journal, 2024)
This study examines the legal system of Emirate Islami Afghanistan, which was established after the Taliban regained power in 2021. It focuses on understanding the structure, foundational documents, and ideological influences that shape the dispensing of justice within the country. The research also explores the processes involved in civil and criminal cases, as well as the methods by which judges are appointed, highlighting their autonomous roles within the judicial system. Data for the study was gathered through in-depth interviews with approximately 15 individuals, including professionals from the Ministry of Justice and legal experts. The study's findings reveal that the Afghan legal system places significant power in the hands of individual judges, who are responsible for both prosecuting and delivering justice. These judges are selected based on their expertise in Hanafi Sharia jurisprudence, which forms the core framework guiding Afghanistan's legal system. The study suggests that the concentration of judicial authority within a single judge reflects a system where legal decisions are heavily influenced by religious interpretations, particularly those rooted in Hanafi thought. This concentration of power and reliance on a specific school of Islamic law highlights the system's distinct approach to governance and justice, differing from more pluralistic or democratic legal frameworks. Ultimately, the research sheds light on how the legal system of Emirate Islami Afghanistan functions, focusing on the role of judges, the influence of Sharia law, and the centralization of legal authority within the country.